Varieties of risk regulation in Europe: coordination, complementarity and occupational safety in capitalist welfare states. (8th September 2017) - Rothstein, Henry; Demeritt, David; Paul, Regine; Beaussier, Anne-Laure; Wesseling, Mara; Howard, Michael; de Haan, Maarten; Borraz, Olivier; Huber, Michael; Bouder, Frederic
Abstract: This article tests the extent to which the organization and stringency of occupational health and safety regulation complements the dominant mode of coordination in the political economy. While the UK explicitly sanctions risk-cost-benefit trade-offs, other European countries mandate ambitious safety goals. That contrast appears to reflect cleavages identified in the Varieties of Capitalism literature, which suggests worker protection regimes are stronger in coordinated market economies than in liberal market economies. Our analysis of Germany, France, UK and the Netherlands, shows that the varied organization of their regulatory regimes is explained through a three-way complementarity with their welfare systems and modes of coordination. However, despite varied headline goals, we find no systematic differences in the stringency of those countries' regulatory protections insofar as they all make trade-offs on safety. Instead, the explicitness, rationalizations and logics of trade-offs vary according to each country's legal system, state tradition and coupling between regulation and welfare system.